Abnormal expression of miR-668-3p in non-small cell lung cancer patients and its correlation with serum-related tumor markers - Wen Yang; Ling Liu; Jianliang Li; Yingchao Liu; Lin Rong; Junjie Ma; Rongchen Li; Qiuyue Zhang; Yugang Liu (Journal of Cardiothoracic Surgery)
Abstract Background The accuracy and reliability of identified biomarkers in differentiating early non-small cell lung cancer (NSCLC) remain suboptimal, thereby impeding the timely detection of NSCLC.The objective of this research is to examine the expression level and diagnostic utility of miR-668-3p in individuals with NSCLC, along with its effectiveness and predictive capacity in the combined diagnosis of early-stage NSCLC using serum markers. Methods The research included 117 NSCLC patients and 101 pulmonary nodule patients (controls). Quantitative PCR was employed to assess the expression levels of miR-668-3p in NSCLC patients. The association between miR-668-3p and clinical characteristics and serum biomarker (AFP, CEA, NSE, and CYFRA21-1) levels in NSCLC patients was examined using chi-square tests and Pearson correlation analyses. The ROC curve analysis was conducted to determine the individual and combined diagnostic efficacy of miR-668-3p and serum biomarkers. Additionally, a logistic regression model was utilized to identify risk factors for lung cancer in patients with pulmonary tuberculosis. Results The expression level of miR-668-3p was down-regulated in early-stage NSCLC patients compared with the control group, and showed a significant association with serum biomarkers related with disease progression, tumor staging, and lymph node metastasis. The combined detection of miR-668-3p and serum markers demonstrated robust diagnostic efficacy for early NSCLC and effective predictive capabilities for lung cancer occurrence in individuals with pulmonary nodules. Conclusions The miR-668-3p has the potential to be a promising biomarker for NSCLC and enhance the accuracy of early NSCLC clinical detection.